Empowerment of Islamic Educational Institutions in Society 5.0 - Rozza, Dian Silvia; Faridi, Faridi; Ishomuddin, Ishomuddin (Green Publisher, 2024)
This research analyzes the differences between Industrial Revolution 4.0 and Society 5.0. It also discusses the empowerment of Islamic educational institutions in the Society 5.0 era. This research uses a qualitative approach with types of literature. The research results show that (1) Industrial Revolution 4.0 emphasizes the power of disruptive technology in the manufacturing industry. However, the Industrial Revolution 4.0 places less emphasis on development aspects for society because it is more focused on the economic realm. Meanwhile, Society 5.0 is a futuristic concept that aims to create intelligent humans with the help of Industry 4.0 technology, and (2) proposals for empowering futuristic educational institutions that would be appropriate in the Society 5.0 era, namely: increasing literacy, multicultural education, entrepreneurship-based education, and character education. These four proposals align with the six profiles of Pancasila students in Indonesia.